Kesepian dan Depresi pada Lansia di Pelayanan Sosial Tresna Werdha (PSTW) Jember, Indonesia - Nadia Monicaputri; Nurul Ulya Luthfiyana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Indonesia is currently undergoing a demographic transition, resulting in an ageing population. The increasing prevalence of mental health problems among older adults is placing greater demands on public health services. This study aims to investigate sociodemographic characteristics and loneliness, as well as examine their association with depression among older adults at the Tresna Werdha Social Services. The cross-sectional study was conducted at PSTW Jember, East Java, from April to June 2023, involving 82 older adults selected using a simple random sampling technique. Data were collected through interviews using a structured questionnaire that included sociodemographic information and mental health–related factors. The instruments used were the DJGLS-11 and GDS-15 to assess loneliness and depression, respectively. Chi-square test of independence was conducted to clarify the association between the variables. The majority of participants were aged 70 years or older (63.40%), female (65.90%), unmarried or widowed (65.90%), and had basic education levels (elementary, junior high, or senior high school equivalents) (96.30%). Most older adults experienced loneliness (80.50%) and depression (75.60%). Bivariate analysis results showed that marital status and loneliness were significantly associated with depression among older adults (OR = 7.50; 95% CI = 1.25–44.68; p-value = 0.029; OR = 70.00; 95% CI = 12.75–384.23; p-value < 0.001). Routine screenings, enhanced personal counseling, and optimized roles for family and staff are essential to support the psychosocial well-being of older adults in the development of social policies.